Coping and adaptation strategies among young persons living with type 1 diabetes and their caregivers: textual and photovoice analyses - Bernard Afriyie Owusu; Prince Ofori-Boateng; David Teye Doku (BMC, 2023)
Abstract Background Management of type 1 diabetes (T1D) is complex and demanding. It requires patients and their caregivers, particularly those in low-resource settings to adopt productive coping strategies to achieve ideal glycaemic control. Coping and adaptation strategies have far-reaching implications on their behavioural and health outcomes. Yet, it is uncertain how young people living with T1D and their caregivers in low-resource settings cope and adapt to the challenges of T1D management. This study analysed textual and photo evidence on the coping and adaptation strategies employed by young persons living with T1D (warriors) and their caregivers in Ghana. Methods Qualitative data were collected from 28 warriors, 12 caregivers, 6 healthcare providers and other stakeholders in southern Ghana using semi-structured interview guides. Participants were identified at T1D support group centres, hospitals, and their places of residence, and recruited into the study using maximum variation and snowball sampling approaches. Data were collected via face-to-face interviews, photovoice, telephone interviews and videoconferencing and were thematically analysed using QSR NVivo 11. Results Four superordinate themes which are productive coping, non-productive coping, keeping T1D a secret, and coping with costs of care were identified. Productive coping entailed condition acceptance, planning ahead, seeking social support, borrowing insulin, and overcoming the barriers of insulin storage. On the other hand, avoidance, disengagement, and re-use of syringes were the common non-productive coping approaches. Due to stigma and discrimination, the warriors shrouded their condition in secrecy. As a response to the financial burden of T1D care, caregivers/patients borrowed money, took loans, and sold household items. Conclusion Young persons living with T1D and their caregivers adopted coping strategies which both promoted and compromised their T1D management. There was an occasional co-existence of diverse coping strategies (productive and non-productive), and these reflects the personal and contextual stressors they faced. The results call for the need to eliminate barriers of T1D management and equip patients and their caregivers with ongoing T1D coping competencies.